(3GdeYhbGJ GdELJeGYjI GdJj JhGLg eYdej GdYdhe aj GdeQMdI GdeJhSWI (B- (3fehPL GdLfhH GddHfGfjs - (3YjSi, Ydj eMeOs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2004)
(3gOaJ GdOQGSI Edi GdcTa Yf GdeYhbGJ GdJj JhGLg eYdej GdYdhe aj GdeQMdI GdeJhSWI aj GdLfhH GddHfGfj (B((3eMGaXJj GdLfhH hGdfHWjI(B)(3, hGdJYQa Ydi GdeDKQGJ GdaGYdI HgPg GdeYhbGJ ef NdGd OQGSI GdYdGbI GdbGFeI Hjf gPg GdeYhbGJ hcd ef eJZjQ GdLfS hfhY GdbWGY hGdJNUU GdYdej hGdYeQ hGdNHQI(B. (3EYJeOJ GdOQGSI efgL OQGSI GdMGdI, hTedJ GdYjfI (B209 (3ef eYdej GdYdhe aj GdeQMdI GdeJhSWI ef GdLfSjf aj LejY GdeOGQS GdeJhSWI GdQSejI hGdNGUI aj eMGaXJj GdLfhH hGdfHWjI hGdHGdZ YOOgG (B150 (3eOQSI (B(53 (3NGUI h (B97 (3QSejI(B). (3hESJNOeJ COGI GdESJeGQI dLeY GdeYdheGJ(B. (3HjfJ GdfJGFL EJaGbkG Hjf eYdej GdYdhe Ydi hLhO eYhbGJ ELJeGYjI JQHhjI JMhd Ohf JMbjb GdCOGA GdJOQjSj HTcd LjO aj GdeQMdI GdeJhSWI aj GdLfhH GddHfGfj, hJCKjQ gPg GdeYhbGJ Ydi COGA GdeYdejf ef LgI, hGdJMUjd GdYdej ddWdGH ef LgI CNQi(B. (3HjfJ GdOQGSI JQJjH GdeYhbGJ MSH GdChdhjI HGdfSHI deYdej GdYdhe, hYOe hLhO aQhbGJ PGJ OdGdI EMUGFjI ef hLgI fXQ GdeYdejf Mhd Jdc GdeYhbGJ fJjLI GdJNUU GdYdej GdCcGOjej, hfJjLI GdENJdGa aj GdbWGY GdQSej hGdbWGY GdNGU, hfJjLI ENJdGa GdLfS(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Cycle moyen L$1 (Benseignement des Sciencess; Intermediate Education Sciences education; Les Facteurs Socio- Economiques; Performance professionnel; Professional performance; Social and Economic Factors; South; Sud; (3GdGOGA Gdegfjs; (3GdLfhHs; (3GdYhGed GdGLJeGYjI hGdGbJUGOjIs; (3GdeQMdI GdeJhSWI JYdje GdYdhes